2017
DOI: 10.1098/rspb.2017.0834
|View full text |Cite|
|
Sign up to set email alerts
|

The growth of finfish in global open-ocean aquaculture under climate change

Abstract: Aquaculture production is projected to expand from land-based operations to the open ocean as demand for seafood grows and competition increases for inputs to land-based aquaculture, such as freshwater and suitable land. In contrast to land-based production, open-ocean aquaculture is constrained by oceanographic factors, such as current speeds and seawater temperature, which are dynamic in time and space, and cannot easily be controlled. As such, the potential for offshore aquaculture to increase seafood produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 57 publications
3
68
0
Order By: Relevance
“…Our results further lend credence to previous findings pointing out that changes in ocean conditions because of climate change would affect the suitable environmental area that supports the farming of aquatic species in open water farming systems (Froehlich et al, ; Klinger et al, ; Oyinlola et al, ). Mariculture species perform best within a stress‐free environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results further lend credence to previous findings pointing out that changes in ocean conditions because of climate change would affect the suitable environmental area that supports the farming of aquatic species in open water farming systems (Froehlich et al, ; Klinger et al, ; Oyinlola et al, ). Mariculture species perform best within a stress‐free environment.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies that investigated climate change effects on the growth potential and availability of suitable marine areas for mariculture (Froehlich, Gentry, & Halpern, 2018;Klinger, Levin, & Watson, 2017) suggest that climate change impact will be heterogeneous across species and regions. Noticeable adverse effects are projected for mariculture-suitable marine areas around the equator with substantial gains towards the poles.…”
mentioning
confidence: 99%
“…Indeed, much applied research is currently focused on "cross-sector" marine spatial planning, which aims to develop policies that optimize the (sustainable) use of the oceans by all sectors, for example fishing, aquaculture, shipping, tourism and oil and mineral extraction (Lester et al, 2013;Klinger et al, 2017). Like in the case of marine spatial planning geared solely for fisheries (e.g., MPAs), cross sector spatial policies will depend on a detailed quantification of spatial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, less competition for space could permit cultivating bivalves at lower stocking densities. Although off-shore aquaculture lacks the physical protection of sheltered bays, by lowering long-lines several meters into the water column, abrasive wave action can be avoided, and more stable temperatures can be achieved (DFO, 2017;Klinger et al, 2017). Preliminary results from M. edulis grown off-shore in Newfoundland indicated that off-shore growth rates were comparable to in-shore growth, and that spawning occurred less often, but was more predictable (DFO, 2017).…”
Section: Limitationsmentioning
confidence: 99%
“…DEB has been parameterized for several bivalve species (e.g., Pouvreau et al, 2006;Crassostrea gigas;van der Veer et al, 2006; Macoma balthica, Mya arenaria, Cerastoderma edule, Mytilus edulis, Crassostrea gigas; Filgueira et al, 2014;Crassostrea virginica) and used to predict their growth (e.g., Lavaud et al, 2017;Crassostrea virginica), and reproductive effort (Montalto et al, 2016; Brachidontes pharaonis, Mytilaster minimus, Mytilus galloprovincialis). The coupling of climate and growth models is being used under the context of climate change to explore the effect of predicted temperatures on the performance and distribution of organisms (e.g., Sarà et al, 2011Sarà et al, , 2013; Brachidontes pharaonis; Thomas et al, 2011Thomas et al, , 2015; Mytilus edulis, Crassostrea gigas; Klinger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%